Review of SIPD Implementation: Impacts on Public Sector Accounting Practices - Rizqi Annisa; Wahyudin Nor (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Local Government Information System (SIPD) has an important role in improving transparency and accountability of local financial reporting. Specific Background: Despite its widespread implementation, empirical evidence on the determinants of SIPD adoption and its downstream impacts is limited, especially in local governments in Indonesia. Knowledge Gaps: Previous research rarely integrates user satisfaction mechanisms with net benefit outcomes using a comprehensive information system success framework. Objective: This study examines the factors that influence SIPD adoption and evaluates their impact on user satisfaction and perceived net benefits. Methods: Using an integrated Information System Success Model (ISSM) and End User Computing Satisfaction (EUCS) framework, data were collected from 193 users in Banjarmasin City, Hulu Sungai Tengah Regency, Barito Kuala Regency, and Hulu Sungai Selatan Regency, and analysed using Structural Equation Modeling (SEM). Results: Information content, ease of use, and timeliness significantly and positively influence user satisfaction, which in turn exerts a significant positive influence on perceived net benefits. Novelty: The application of SEM within the integrated ISSM-EUCS framework in a public sector context is a methodological contribution. Implications: The findings provide actionable insights for local governments to strengthen transparency and accountability by optimising SIPD design and implementation strategies.